Is Muscular Fitness Associated with Future Health Benefits in Children and Adolescents? A Systematic Review and Meta-Analysis of Longitudinal Studies - García-Hermoso, Antonio; Ramírez-Campillo, Rodrigo; Izquierdo, Mikel (Sports medicine (Auckland), 2019)
Background No previous systematic review has quantitatively examined the association between muscular fitness during childhood and adolescence and health parameters later in life. Objective The aim was to systematically review and meta-analyze the current evidence for a prospective association between muscular fitness in childhood and adolescence and future health status. Methods Two authors systematically searched MEDLINE, EMBASE and SPORTDiscus electronic databases and conducted manual searching of reference lists of selected articles. Relevant articles were identified by the following criteria: apparently healthy children and adolescents aged 3–18 years with muscular fitness assessed at baseline (e.g., handgrip, standing long jump, sit-ups, among others), and a follow-up period of ≥ 1 year. The outcome measures were anthropometric and adiposity measurements and cardiometabolic, bone and musculoskeletal health parameters. Two authors independently extracted data. Results Thirty studies were included in the meta-analysis, yielding a total of 21,686 participants. The meta-analysis found a significant, moderate-large ( p < 0.05) effect size between muscular fitness at baseline and body mass index ( r = − 0.14; 95% confidence interval (CI) − 0.21 to − 0.07), skinfold thickness ( r = − 0.32; 95% CI − 0.40 to − 0.23), homeostasis model assessment estimated insulin resistance ( r = − 0.10; 95% CI − 0.16 to − 0.05), triglycerides ( r = − 0.22; 95% CI − 0.30 to − 0.13), cardiovascular disease risk score ( r = − 0.29; 95% CI − 0.39 to − 0.18), and bone mineral density ( r = 0.166; 95% CI 0.086 to 0.243) at follow-up. Conclusion A prospective negative association was observed between muscular fitness in childhood/adolescence and adiposity and cardiometabolic parameters in later life, together with a positive association for bone health. There is inconclusive evidence for low back pain benefits.